The Effect of Using the Tiktok Social Platform on the Communication Behavior of Modern Society - Ardiansyah, Fiqih; Ashori, Muhammad Aqbal; Aditya, Rangga; Wihayati, Welly (ann4publisher@gmail.com, 2025)
Background. The development of the times from year to year cannot be separated from the internet. The internet also influences the rapid advancement of communication technology. One example of advances in communication technology is the digitization of media or social media platforms such as TikTok. Aim. This research aims to find out how TikTok's social media platforms affect people's communication patterns. Methods. This research uses multiple linear regression analysis, which was conducted using the SPSS application data processing tool. Questionnaires were distributed to 80 people in Sumber District to obtain primary data. Result. According to the study's findings, the digitization of social media platforms like TikTok significantly impacts people's behavior in Sumber District. In addition to being a marketplace for goods and services, educational institutions can use TikTok as an interactive learning tool to enhance education and promote MSME goods in the Sumber District community. Conclusion. However, TikTok also has a detrimental effect on its users, as shown by the lack of ethics and disdain for parents. Implication. Therefore, every community needs to have self-control and management in using the TikTok application.